Large diversity in the O-chain biosynthetic cluster within populations of Pelagibacterales - Jose M. Haro-Moreno; Mario López-Pérez; Carmen Molina-Pardines; Francisco Rodriguez-Valera (mBio)
ABSTRACT Genomic diversity in prokaryotic species is largely due to the existence of extensive pangenomes, allowing different gene complements to be drawn depending on the strain. Here, we have studied the diversity of the O-chain polysaccharide biosynthesis cluster (OBC) in marine bacteria of the Pelagibacterales order as a proxy to measure such genetic diversity in a single population. The study of single-amplified genomes (SAGs) from the whole order found a pattern similar to that of other well-studied microbes, such as the Enterobacteriales or Alteromonas, where distinct OBCs represent strains containing different gene pools. We found that most of the OBC sharing happened among individuals of the same clonal frame (>99% average nucleotide identity). Moreover, given the parsimonious way this cluster changes, the diversity of the OBCs can be extrapolated to the size of the population’s pangenome. This assumes that different OBCs correspond to lineages containing unique flexible gene pools, as seen in the aforementioned microbes. Through long-read metagenomics, we could detect 380 different OBCs at a single Mediterranean sampling site. Within a single population (single species and sample) of the endemic Ia.3/VII (gMED) genomospecies, we identified 158 OBCs, of which 130 were unique. These findings suggest that the gene pool within a single population might be substantial (several thousands). While this figure is large, it aligns with the complexity of the dissolved organic matter that these organisms can potentially degrade.IMPORTANCEDifferent strains of the same bacterial species contain very different gene pools. This has been long known by epidemiologists. However, it is unknown what gene pool is present in a single set of environmental conditions, i.e., the same time and place in free-living bacteria. Here, we have leveraged information from SAGs to analyze the diversity of the gene cluster coding for the O-chain polysaccharide, a typical component of the flexible gene pool classically used as a tool to differentiate strains in clinical microbiology. It evolves at a similar rate to the rest of the genome and does not seem to be affected by an arms race with phages. One single species of Pelagibacteriales (gMED) revealed an astounding diversity in one sample studied by long-read metagenomics. Our results point to a large gene pool (local pangenome) present in a single population, which is critical to interpreting the biological meaning of the pangenome, i.e., it provides intrapopulation diversity rather than characterizing strains with different distribution in time and/or space.